Photochemical permutation of meta-substituted phenols - Maialen Alonso; Giovanni Lonardi; Enrique M. Arpa; Baptiste Roure; Alessandro Ruffoni; Daniele Leonori (Nature Communications)
Abstract Phenols and their derivatives are highly relevant motifs in pharmaceuticals, natural products, and other functional materials. Conventional strategies for phenol synthesis rely on classical aromatic functionalization, which is often dictated by electronic and steric factors. Herein, we report an alternative approach for phenol synthesis where irradiation in the presence of Lewis or Brønsted acids enables the selective migration of alkyl and aryl groups from meta to either the ortho or para positions. This method exploits the intrinsic photochemical properties of phenolic arenium ions and their rearrangement via 4π electrocyclization and following “1,2-methylene shift”. By leveraging selective photoexcitation of these species, we can achieve precise control over the directionality of the permutation process. Specifically, short-wavelength irradiation (λ = 310 nm) promotes meta→para migration, while longer-wavelength irradiation (λ = 390 nm) meta→ortho. This approach offers a late-stage method to use readily available phenols as templates for the preparation of other isomers without de novo synthesis. The applicability of the method has been demonstrated on the isomerization of poly-substituted derivatives including some bioactive species.